A Critical Review “Phenomenology and Mysticism” - Yahya Solati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article criticizes the book “Phenomenology and Mysticism”  by Anthony J. Steinbock. The writer has tried to identify religious and mystical experiences by the use of phenomenological’s style and helping from concepts such as “evidence”, “phenomenological’s reduction” and “intention”. Steinbock’s main concern is to consider the reaction between the phenomenology and theology to make a connection and relation among the vast range of religious beliefs with philosophical problems such as “evidence”, “selfhood”, and “otherness”. Lack of stability in his point of view, inability in sufficient analysis, contradiction in terms, etc. weaken his attitude in this book. Furthermore, this book contains problems in content and writing considered as a serious downsides of the book